Mengenalkan Lagu Nasional dan Lagu Daerah kepada Anak Migran Indonesia di Malaysia sebagai Upaya Pelestarian Identitas Kebangsaan - Amadea Choirul Nisa; Edy Purwanto (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
This community service program aimed to introduce Indonesian national and regional folk songs to Indonesian migrant children at Sanggar Bimbingan (SB) Pandan Jaya, Kuala Lumpur, Malaysia. Held on 30 October 2025, the activity involved 20 children aged 9–12 years who initially had very limited knowledge of Indonesian culture due to stronger exposure to Malaysian popular media. The intervention used a simple audiovisual approach by screening videos of four regional songs (Rasa Sayange, Jali-Jali, Ampar-Ampar Pisang, Es Lilin) and three national anthems (Indonesia Raya, Bagimu Negeri, Hari Merdeka). Children then received short explanations about each song’s origin and meaning before participating in group singing sessions. Pre-test findings showed that only 15% of participants could name a single regional song and none knew a complete national anthem. After the activity, results improved markedly: all children were able to identify at least three regional songs with their origins and all three national anthems, 85% could accurately sing the refrains, and 95% instinctively stood in respect when Indonesia Raya was played. Enthusiasm was consistently high, and students expressed pride in their Indonesian identity. Attention challenges were managed using quick quizzes and small rewards. Seven high-quality song videos were donated as permanent learning materials, ensuring lasting cultural impact.